High night temperature effects on wheat and rice: Current status and way forward - Impa, Somayanda M.; Raju, Bheemanahalli; Hein, Nathan T.; Sandhu, Jaspreet; Prasad, P.V. Vara; Walia, Harkamal; Jagadish, Krishna S.V. (Wiley, 2021)
Rapid increases in minimum night temperature than in maximum day temperature is predicted to continue, posing significant challenges to crop productivity. Rice and wheat are two major staples that are sensitive to high night‐temperature (HNT) stress. This review aims to (i) systematically compare the grain yield responses of rice and wheat exposed to HNT stress across scales, and (ii) understand the physiological and biochemical responses that affect grain yield and quality. To achieve this, we combined a synthesis of current literature on HNT effects on rice and wheat with information from a series of independent experiments we conducted across scales, using a common set of genetic materials to avoid confounding our findings with differences in genetic background. In addition, we explored HNT‐induced alterations in physiological mechanisms including carbon balance, source–sink metabolite changes and reactive oxygen species. Impacts of HNT on grain developmental dynamics focused on grain‐filling duration, post‐flowering senescence, changes in grain starch and protein composition, starch metabolism enzymes and chalk formation in rice grains are summarized. Finally, we highlight the need for high‐throughput field‐based phenotyping facilities for improved assessment of large‐diversity panels and mapping populations to aid breeding for increased resilience to HNT in crops.